Classification and practical approach to the diagnosis and management of hypersensitivity to nonsteroidal anti‐inflammatory drugs. Issue 10 (5th October 2013) - Kowalski, M. L.; Asero, R.; Bavbek, S.; Blanca, M.; Blanca‐Lopez, N.; Bochenek, G.; Brockow, K.; Campo, P.; Celik, G.; Cernadas, J.; Cortellini, G.; Gomes, E.; et al.
Abstract Hypersensitivity reactions to aspirin (acetylsalicylic acid) and other nonsteroidal anti‐inflammatory drugs (NSAIDs) constitute only a subset of all adverse reactions to these drugs, but due to their severity pose a significant burden to patients and are a challenge to the allergist. In susceptible individuals, NSAIDs induce a wide spectrum of hypersensitivity reactions with various timing, organ manifestations, and severity, involving either immunological (allergic) or nonimmunological mechanisms. Proper classification of reactions based on clinical manifestations and suspected mechanism is a prerequisite for the implementation of rational diagnostic procedures and adequate patient management. This document, prepared by a panel of experts from the European Academy of Allergy and Clinical Immunology Task Force on NSAIDs Hypersensitivity, aims at reviewing the current knowledge in the field and proposes uniform definitions and clinically useful classification of hypersensitivity reactions to NSAIDs. The document proposes also practical algorithms for the diagnosis of specific types of NSAIDs hypersensitivity (which include drug provocations, skin testing and in vitro testing) and provides, when data are available, evidence‐based recommendations for the management of hypersensitive patients, including drug avoidance and drug desensitization.